Dinamika Model Pemerintahan dalam Masyarakat Melayu Islam Jambi: Studi Kasus Kabupaten Bungo - Harun, Hermanto; Sagala, Irmawati (Kontekstualita, 2013)
Before the establishment of Republic of Indonesia (NKRI), this archipelago has been lived by variety of traditional governance models that remain autonomous in its homeland, generally recognized as the smallest administrative units. The autonomy of the local government then crippled by the New Order Government policy with the issuance of the enacment No. 5 of 1979 called âPemerintahan Desaâ. Through this enacment, the smallest model of governments homonized into âDesaâ. The Province of Jambi is one of the areas affected by the enactment No. 5 of 1979 about âDesaâ. Previously, people in Jambi has a traditional governance model in some regions called Dusun. This traditional form of government then turned into the village after 1979. This paper discusses the dynamics of the smallest unit in Jambi administration with case studies in Bungo District. The discussion begins with a description of traditional governance model that exist in Jambi and amendment after 1979. The opportunities of applying traditional governance models back in the era of regional autonomy with the release of a case study Bungo Government Regulation No. 9 of 2007 on the Village Head being mention Rio, Village or Desa Being Dusun, Hamlet Being Kampung will also be discussed at the end of this paper. Formally, the birth of this regulation affect the reinforcement of the traditional Malay Jambi, among others in the form of leadership, conflict management and strengthening of indigenous socialization. Keywords: model pemerintahan, dusun, rio.